Legal Strategy To Prevent And Overcome Abuse Of Funds In Digital Wallets - Maharani Trisni Zulaiha; Lamijan Lamijan; Hono Sejati (Al-Makki Publisher, 2024)
E-wallet, or electronic wallet, is an application or software that enables users to store, manage, and conduct financial transactions electronically. E-wallets usage is able for various purposes, such as making payments, transferring money, or storing payment information for online transactions. Despite the advantages of e-wallets, there are still risks associated with their use, such as the potential loss of consumer funds and the possibility of personal data leaks due to inadequate security measures on the platform. It can disadvantage consumers as users of e-wallets. Law Number 8 of 1999 concerning Consumer Protection contains various provisions aimed at directing manufacturers and businesses, especially those in the business sector, to behave in a manner that supports national economic development. Bank Indonesia has implemented a legal protection system for digital wallet users, starting from the issuance of regulations and policies. One such policy is the creation of guidelines for the operation of payment system services, especially for the use of digital wallets. These guidelines are regulated in Bank Indonesia Regulation Number 20/6/PBI/2018, which discusses the operation of payment systems through digital wallets. This regulation, known as the Bank Indonesia Electronic Money Regulation, establishes licensing and supervision procedures for electronic money operations, including the use of digital wallets. Bank Indonesia not only regulates operational procedures but also emphasizes consumer protection for payment system users, including those using digital wallets, by issuing Bank Indonesia Regulation Number 16/1/PBI/2014 concerning Consumer Protection for Payment System Providers.